SAT0218 Efficacy and safety of baricitinib in mtx-ir patients with rheumatoid arthritis: 52 week results from a phase 3 study (RA-BALANCE). (12th June 2018) - Li, Z.; Hu, J.; Bao, C.; Li, X.; Li, X.; Xu, J.; Spindler, A.; Zhang, X.; Xu, J.; Li, Z.; Wang, G.; Sun, J.; et al.
Abstract : Background: Baricitinib (BARI) is an oral selective inhibitor of Janus kinase 1 (JAK1) and JAK2. In the EU and some other countries, baricitinib has been approved for the treatment of moderately to severely active rheumatoid arthritis (RA) in adult patients. This abstract reports efficacy and safety results from a phase 3, double-blinded, 52-week study (RA-BALANCE) that enrolled patients (pts) in China, Argentina and Brazil (NCT02265705 ). Objectives: To assess the efficacy and safety of BARI vs placebo (PBO) in the treatment of RA. Methods: Patients with moderately to severely active RA (tender joint counts ≥6 & swollen joint counts ≥6 & hsCRP≥6 mg/L) despite stable background methotrexate (MTX), were randomized 1:1 to PBO (n=145) or BARI 4-mg (n=145) once daily (QD), stratified by country and baseline joint erosion status. Background MTX was continued. Non-responders were rescued from Week 16. At Week 24, pts receiving PBO were switched to BARI 4-mg QD. ACR20 at Week 12 was the primary endpoint and there were multiple secondary endpoints e.g., assessing physical function, low disease activity and pain. Results: The primary ACR20 response was significantly greater for BARI than PBO (58.6% vs 28.3%, p≤0.001, Table). At Weeks 12 and 24, significant improvements were seen in pts receiving BARI vs PBO for ACR20/50/70, DAS28-hsCRP, CDAI low disease activity and SDAI low disease activity, many as early as by Week 1. At Week 16, significantly less radiographic progression was seen in pts receiving BARI vs PBO and numerical improvement was observed at Week 24. At Week 12, significant improvement in HAQ-DI minimum clinically important difference ≥0.3 (physical function), duration of morning joint stiffness, severity of morning joint stiffness numeric rating scale (NRS), worst tiredness NRS and reduced pain (0–100 mm VAS) were seen in pts receiving BARI vs PBO. During Weeks 0–24, treatment emergent adverse events and infections were reported in 74.5% and 42.1% of BARI pts and 62.1% and 28.3% of PBO pts, respectively. Serious adverse events were reported in 2.8% of pts in both groups. There was 1 nonserious esophageal candidiasis in the BARI group for Week 0–24. Four herpes zoster events (1 PBO, 3 BARI) were reported for Week 0–24. No major cardiovascular events, deaths, tuberculosis, venous thromboembolic events or malignancies were reported in the study through Week 24 for PBO and through Week 52 for BARI group. No unexpected safety signals were observed. Conclusions: Compared to PBO, BARI provided significant improvements in control of signs and symptoms, including pain and physical function with an acceptable safety profile. Disclosure of Interest: Z. Li Consultant for: Advisory board member of baricitinib, J. Hu: None declared, C. Bao Consultant for: Advisory board member of baricitinib, X. Li Consultant for: Advisory board member of baricitinib, X. Li Consultant for: Advisory board member of baricitinib, J. Xu: None declared, A. Spindler: None declared, X. Zhang Consultant for: Advisory board member of baricitinib, J. Xu Consultant for: Advisory board member of baricitinib, Z. Li Consultant for: Advisory board member of baricitinib, G. Wang Consultant for: Advisory board member of baricitinib, J. Sun Shareholder of: Eli Lilly and company, Employee of: Eli Lilly and company, F. Ji Shareholder of: Eli Lilly and company, Employee of: Eli Lilly and company, H. Tao Shareholder of: Eli Lilly and company, Employee of: Eli Lilly and company, L. Zhan Employee of: Eli Lilly and company, T. Rooney Shareholder of: Eli Lilly and company, Employee of: Eli Lilly and company, C. Zerbini Grant/research support from: Grants for research received by my research center CEPIC, for teriparatide and baricitinib protocols, Consultant for: Advisory board member of baricitinib